Exosomal transfer of long non-coding RNA SBF2-AS1 enhances chemoresistance to temozolomide in glioblastoma - Zhang, Zhuoran (J Exp Clin Cancer Res, 2019)
BACKGROUND: Acquired drug resistance is a constraining factor in clinical treatment of glioblastoma (GBM). However, the mechanisms of chemoresponsive tumors acquire therapeutic resistance remain poorly understood. Here, we aim to investigate whether temozolomide (TMZ) resistance of chemoresponsive GBM was enhanced by long non-coding RNA SBF2 antisense RNA 1 (lncRNA SBF2-AS1) enriched exosomes. METHOD: LncSBF2-AS1 level in TMZ-resistance or TMZ-sensitive GBM tissues and cells were analyzed by qRT-PCR and FISH assays. A series of in vitro assay and xenograft tumor models were performed to observe the effect of lncSBF2-AS1 on TMZ-resistance in GBM. CHIP assay were used to investigate the correlation of SBF2-AS1 and transcription factor zinc finger E-box binding homeobox 1 (ZEB1). Dual-luciferase reporter, RNA immunoprecipitation (RIP), immunofluorescence and western blotting were performed to verify the relation between lncSBF2-AS1, miR-151a-3p and XRCC4. Comet assay and immunoblotting were performed to expound the effect of lncSBF2-AS1 on DNA double-stand break (DSB) repair. A series of in vitro assay and intracranial xenografts tumor model were used to determined the function of exosomal lncSBF2-AS1. RESULT: It was found that SBF2-AS1 was upregulated in TMZ-resistant GBM cells and tissues, and overexpression of SBF2-AS1 led to the promotion of TMZ resistance, whereas its inhibition sensitized resistant GBM cells to TMZ. Transcription factor ZEB1 was found to directly bind to the SBF2-AS1 promoter region to regulate SBF2-AS1 level and affected TMZ resistance in GBM cells. SBF2-AS1 functions as a ceRNA for miR-151a-3p, leading to the disinhibition of its endogenous target, X-ray repair cross complementing 4 (XRCC4), which enhances DSB repair in GBM cells. Exosomes selected from temozolomide-resistant GBM cells had high levels of SBF2-AS1 and spread TMZ resistance to chemoresponsive GBM cells. Clinically, high levels of lncSBF2-AS1 in serum exosomes were associated with poor response to TMZ treatment in GBM patients. CONCLUSION: We can conclude that GBM cells remodel the tumor microenvironment to promote tumor chemotherapy-resistance by secreting the oncogenic lncSBF2-AS1-enriched exosomes. Thus, exosomal lncSBF2-AS1 in human serum may serve as a possible diagnostic marker for therapy-refractory GBM. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13046-019-1139-6) contains supplementary material, which is available to authorized users.